THE HIDDEN REASON OF ED BOONE TO KILL THE DOG IN MARK HADDON’S THE CURIOUS INCIDENT OF THE DOG IN THE NIGHT-TIME - Ajeng, Galuh Dwi (Lentera: Jurnal Ilmiah Kependidikan, 2014)
This study discusses the hidden reason of disastrous action conducted by Ed Boone, one of the main characters in The Curious Incident of the Dog in the Night-Time. This study aims to find Ed Boone’s hidden reasons for killing the dog. The sources in this study are taken from books and the internet. The novel, Mark Haddon’s The Curious Incident of the Dog in the Night-Time is used as the main source. This study uses psychological approach. The theories used are theory of character, characterization and theory of psychology. In theory of psychology, the writer uses Freud’s personality structure and defense mechanisms. The finding of this study is: Ed Boone’s hidden reason to kill the dog is because of jealousy, disappointment, anger that his needs to love and to be loved are denied. These feelings come from his unconscious conflicts that are due to his relation with Mrs. Boone, Mr. Shears and Mrs. Shears. These lead him to kill the dog. Thus his action is to release his anger.